Management interventions of pearl millet systems for attaining cereal self-sufficiency in Senegal - Vieira Junior, Nilson; Carcedo, Ana Julia Paula; Min, Doohong; Diatta, Andre Amakobo; Araya, Alemie; Prasad, P. V. Vara; Diallo, Amadiane; Ciampitti, Ignacio (Frontiers in Sustainable Food Systems, 2024)
Critical management interventions to target the yield potential for each environment are key to food security and increasing the resilience of current agricultural systems in Senegal. Cereal production is highly dependent on pearl millet (Pennisetum glaucum L.) rainfed systems, as one of the major field crops for smallholders. This study aims to i) quantify the production of pearl millet at the department level for the last quinquennial (until 2020), ii) assess the impact of weather (temperature and precipitation) on the millet-based supply of cereal demand, and iii) investigate, through crop modeling, the impact of millet-based supply of cereal demand by comparing recommended management interventions to smallholder-based strategies at the department level. Millet-based cereal supplydemand was estimated considering the observed population and the supply via the simulated pearl millet production (obtained using APSIM-Millet model) at the department level over the period from 1990 to 2021. High temperature and low precipitation occurrence presented a frequency of 35% across departments, leading to a reduction of millet production by roughly 6% relative to the normal average for 32 years. Adoption of recommended management showed the potential to increase the millet supply, more than doubling the current cereal supply, closing the current supply-demand gap (89 kg inhabitant -1 ). Achieving future cereal self-sufficiency will also require an intensification of other cereals production.